LEFT ATRIAL TO AORTIC ROOT INDICES USING TWO‐DIMENSIONAL AND M‐MODE ECHOCARDIOGRAPHY IN CAVALIER KING CHARLES SPANIELS WITH AND WITHOUT LEFT ATRIAL ENLARGEMENT - Kerstin Hansson; Jens Häggström; Clarence Kvart; Peter F. Lord (2002)
Two‐dimensional (2‐D) echocardiographic measurement of the left atrium (LA) has the potential to be more accurate than the standard M‐mode method, because the LA body can be measured. We evaluated a 2‐D method for measuring LA and aorta (AO) in a right parasternal short‐axis view and compared it to the M‐mode method. An index for LA size (LA/AO) was calculated in 166 cavalier King Charles spaniels, 56 normal and 110 dogs with mitral regurgitation (MR) of varying degrees secondary to chronic valvular disease. In normal dogs, the AO‐2‐D and LA/AO‐2‐D did not correlate to body weight (BW) or BW2; whereas, all M‐mode values and the LA‐2‐D were significantly ( p < .05) related to both BW parameters. In normal dogs, there was no difference between M‐mode and 2‐D indices. For all dogs (normal and dogs with MR) there was an 11% bias between the M‐mode and 2‐D index with the LA/AO‐2‐D being higher than the LA/AO‐M. The association between the mean and the difference of the indices demonstrated a quadratic relationship. Dogs with a mean LA/AO of 2.0–2.5 showed the largest difference between the two indices. Small values for the 2‐D coefficients of variation for respiration and stage of diastole were found; 3.4 and 3.1%, respectively. The 2‐D index is more sensitive to LA enlargement than the M‐mode index.